2019
DOI: 10.1080/14680629.2019.1645725
|View full text |Cite
|
Sign up to set email alerts
|

The use of solubility parameters and free energy theory for phase behaviour of polymer-modified bitumen: a review

Abstract: Advances related to the use of solubility parameters and free energy theory for the phase behaviour study of polymer-modified bitumen (PMB) are reviewed in this paper. The origin and effects of PMB phase behaviour are criticised with a focus on PMB storage stability, morphology and swelling ratio. An overview of the solubility approach for studying PMB is given regarding the historical and future developments. Free energy expressions for PMB systems are analysed, including the free energy of mixing, elastic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 84 publications
(106 reference statements)
0
12
0
2
Order By: Relevance
“…It is reported that the total solubility parameters of NR and SBR are around 16.9 and 18.1 MPa 0.5 , respectively (Mark et al 2013). In addition, solubility parameters for bitumens are in the range 17.2-18.8 MPa 0.5 (Zhu et al 2019). Thus, the similarity between the solubility parameters of bitumen and natural and SR indicates that bitumen is a swelling agent of both rubbers.…”
Section: Effect Of Bitumen Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is reported that the total solubility parameters of NR and SBR are around 16.9 and 18.1 MPa 0.5 , respectively (Mark et al 2013). In addition, solubility parameters for bitumens are in the range 17.2-18.8 MPa 0.5 (Zhu et al 2019). Thus, the similarity between the solubility parameters of bitumen and natural and SR indicates that bitumen is a swelling agent of both rubbers.…”
Section: Effect Of Bitumen Characteristicsmentioning
confidence: 93%
“…The solubility parameter of the polymer is taken as the d value of the solvent which enables the maximum extent of swelling (Redelius 2000(Redelius , 2004. Comparing to the average solubility parameter values, the solubility body of a material in the three-dimensional Hansen space is more realistic and useful (Zhu et al 2019).…”
Section: The Flory-huggins Parametermentioning
confidence: 99%
“…This phenomenon can be explained by the solubility parameter. The solubility parameter ( δ ) of a material can be calculated according to Small equation: 28,29 δ=normalΔEV1/2=ρFiM0 where E is the cohesive energy, V is the molar volume, F i represents the group attraction constant, ρ stands for the density of polymer and M 0 represents the average molar weight of the repeating unit.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the rubber samples were first immersed in a naphthenic oil at elevated temperatures to examine if there is dissolution of rubber taking place during the swelling process. The naphthenic oil has a Hildebrand solubility parameter of 18.5 MPa 0.5 , which is closer to truck tire rubber (18.6 MPa 0.5 ) than most bitumen components (in the range from 17.2 to 18.8 MPa 0.5 ) (12,14,15). Therefore, it is easier for rubber to dissolve into the naphthenic oil than bitumen based on the solubility theory.…”
Section: Does the Rubber Dissolve Into Bitumen? Study Of Rubber In Namentioning
confidence: 96%